MECHANISMS OF DEVELOPMENT OF EFFECTIVENESS OF SOCIAL LIFE ADAPTATION OF DISABLED TEENAGERS (American Journal of Interdisciplinary Research and Development, 2024)
This article is specially enriched in terms of improving the mechanisms of adaptation of deaf and hard of hearing children with disabilities to social life in families.